Current issues of modern traumatology and orthopedics - Golovakha, Maksym (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2025)
On April 11, 2025, a scientific and practical conference “Current Issues of Modern Traumatology and Orthopedics” was held in Zaporizhzhia, organized by the Zaporizhzhia State Medical and Pharmaceutical University together with the NGO “Zaporizhzhia Regional Association of Orthopedists and Traumatologists”.